Tectonophysical analysis and geodynamic interpretation of the three-dimensional geophysical model of the Ukrainian Shield - O.B. Gintov; I. K. Pashkevich (Геофизический журнал, 2010)
Geodynamic features of the Ukrainian Shield (USh) from Early Precambrian to Phanerozoic have been considered based on tectonophysical analysis of complex geophysical 3D model of the Shield, produced at the Institute of Geophysics of the National Academy of Sciences of Ukraine. In accordance with the materials of tectonophysical studies it has been established that fault zones of the USh with initial stages in Neo-Archean and Paleo-Proterozoic were the large shift zones appeared under the action of tangential forces. Kinematics of shift zones was different in the western and eastern megablocks of the Shield that was the basis for conclusion of the absence of connection between its western and eastern parts in Early Precambrian. Tectonophysical materials support the data of paleomagnetism on the clockwise 90 degrees rotation of the Shield together with the East European platform (EEP) as to rotation axis of the Earth during Phanerozoic. Large listric fault zones going to 100 and more km as well as low-angle crust faults which formation accompanied the process of collision of mega-structures of Fennoscandia and Sarmatia were established by deep seismic sounding. The data of seismotomography indicate the lowangle dipping of relatively high-velocity lithosphere of southwestern edge of EEP under relatively low-velocity lithosphere of the adjacent plates. The obtained data testify the fact that the processes of USh crust and mantle formation took place under the action of plate tectonics mechanisms. And it would be overbold at the same time to use the whole set of plate tectonics mechanisms, for example, spreading, formation of oceanic crust, island arches, subduction etc. to the narrow band of the shield as some geologists do. Predominant horizontally shearing type of the most steeply-falling Early Precambrian fault zones of the USh testify the fact that that these zones were transform ones and were formed as a result of the processes of spreading and collision happened outside the Ush.